Voltage Control of Autonomous Power Supply Systems Based on PID Controller Under Unbalanced and Nonlinear Load Conditions; Radio Electronics, Electrical and Power Engineering (REEPE) - Aboelsaud Raef S. S. A. Siam Sayed Ahmed (2019, 2019)
Title screen